Upscaling of mass and heat transport applied to reactive packing catalytic porous media. (16th January 2023) - Luévano-Rivas, O.A.; Quiroz-Ramirez, J.J.; Suarez-Toriello, V.A.; Huerta-Rosas, B.; Sánchez-Ramirez, E.; Segovia-Hernández, J.G.
Highlights: The volume averaging method is used to upscaling the reactive catalytic packing. The computed effective coefficients include the effect of the structure of the catalytic pellets. The upscaled model is validated with comparisons with pore-scale simulations of the catalyst layer. The upscaled model as inputs in reactive multi-scale processes is plausible. Abstract: In various intensified processes, the presence of reactive catalytic packing is essential. These can be visualized as multiscale systems where a diverse mass, energy transfer, and chemical reaction occurs in the catalytic porous medium (i.e., the catalyst layer). This reactive microscopic scale structure influences efficiency. Given the hierarchical nature of the packing in the intensification systems, this paper proposes the derivation of an upscaled model that describes the first-order surface chemical reaction process in this catalyst layer. The upscaling is carried out using the volume averaging theory. The resulting model includes effective coefficients which depend on the transport and reaction parameters influenced by the unit cell geometry. The model is validated by comparing average temperature and concentration profiles obtained from numerical experiments using pore representations of a catalyst packing. The results show the effective parameters that can be used to design catalytic structures in the intensified process.